Pengembangan LKPD tentang Biodiversitas Vegetasi Rawa Berbasis Kearifan Lokal Desa Burai Terintegrasi Model Inkuiri Terbimbing - Yetty Hastiana; Bella Anjelia; Astrid Sri Wahyuni Sumah (Jurnal Penelitian Pendidikan IPA, 2025)
Contextual and environment-based science learning remains a challenge, especially in enhancing students' science process skills (SPS). At MTs Nurul Ula Desa Burai, the lack of learning materials based on environmental exploration and the minimal use of active learning models pose obstacles. However, the swamp ecosystem in Desa Burai is rich in biodiversity and can be utilized as a learning resource. This study aims to develop a guided inquiry-based LKPD incorporating swamp vegetation biodiversity to improve SPS. Using the R&D method with the 4D model (Define, Design, Develop, Disseminate), the study involved seventh-grade students at MTs Nurul Ula Desa Burai. The results show that the LKPD is highly valid (94.74%), practical for students (75%) and teachers (95%), and effective in enhancing SPS based on observation, pretest and posttest results. In conclusion, this LKPD is valid, practical, and effective while also promoting and preserving the local wisdom of Desa Burai.